Idebenone Regulates Aβ and LPS-Induced Neurogliosis and Cognitive Function Through Inhibition of NLRP3 Inflammasome/IL-1β Axis Activation - Lee, Hyun-ju; Park, Jin-Hee; Hoe, Hyang-Sook (Frontiers in Immunology, 2022)
Idebenone is an analogue of coenzyme Q10, an electron donor in the mitochondrial electron transport chain, and thus may function as an antioxidant to facilitate mitochondrial function. However, whether idebenone modulates LPS- and Aβ-mediated neuroinflammatory responses and cognitive function in vivo is unknown. The present study explored the effects of idebenone on LPS- or Aβ-mediated neuroinflammation, learning and memory and the underlying molecular mechanisms in wild-type (WT) mice and 5xFAD mice, a mouse model of Alzheimer’s disease (AD). In male and female WT mice, idebenone upregulated neuroprotective NRF2 expression, rescued LPS-induced spatial and recognition memory impairments, and reduced NLRP3 priming and subsequent neuroinflammation. Moreover, idebenone downregulated LPS-mediated neurogliosis, reactive oxygen species (ROS) levels, and mitochondrial function in BV2 microglial cells and primary astrocytes by inhibiting NLRP3 inflammasome activation. In 5xFAD mice, idebenone increased neuroprotective NRF2 expression and improved amyloid beta (Aβ)-induced cognitive dysfunction. Idebenone downregulated Aβ-mediated gliosis and proinflammatory cytokine levels in 5xFAD mice by modulating the vicious NLRP3/caspase-1/IL-1β neuroinflammation cycle. Taken together, our results suggest that idebenone targets neuroglial NLRP3 inflammasome activation and therefore may have neuroprotective effects and inhibit the pathological progression of neuroinflammation-related diseases.